The EU's new competition policy standards: In search of effects-based, economically intuitive or efficient rules? - Ralf Boscheck (Intereconomics, 2009)
In a 2008 article in the EU's Competition Policy Newsletter, Peter Lowe, Director General of the EU Commission's Directorate Competition, synthesised the experience of his office with regard to the design of competition policy institutions for the 21st century. A year earlier, he had co-authored another article, appearing in the same venue, recapitulating the Commission's lessons learned from the Energy Sector Inquiry and the need for effective unbundling of energy transmission networks. The reader of both, at first astounded by the apparent gap between policymaking reality and reflections upon it, soon detects a rather pragmatic approach to shaping regulatory agendas. But are there limits to expediency?
Keywords: 330